2010
DOI: 10.1007/s11701-010-0191-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety of robotic general surgery in elderly patients

Abstract: As the life expectancy of people in Western countries continues to rise, so too does the number of elderly patients. In parallel, robotic surgery continues to gain increasing acceptance, allowing for more complex operations to be performed by minimally invasive approach and extending indications for surgery to this population. The aim of this study is to assess the safety of robotic general surgery in patients 70 years and older. From April 2007 to December 2009, patients 70 years and older, who underwent vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…26 Likewise, we have recently shown that robotic general surgery and more specifically robotic pancreaticoduodenectomy can be performed safely in patients older than 70 years. 8,11 Yet, in the present study, using the univariate analysis, age greater than 70 years was found to be a risk factor for increased morbidity and mortality. As a result, it is believed that elderly patients should be considered as a population at risk for complications, even if the multivariate analysis failed to demonstrate an independent relationship.…”
Section: Patients' Physiological Statuscontrasting
confidence: 45%
See 1 more Smart Citation
“…26 Likewise, we have recently shown that robotic general surgery and more specifically robotic pancreaticoduodenectomy can be performed safely in patients older than 70 years. 8,11 Yet, in the present study, using the univariate analysis, age greater than 70 years was found to be a risk factor for increased morbidity and mortality. As a result, it is believed that elderly patients should be considered as a population at risk for complications, even if the multivariate analysis failed to demonstrate an independent relationship.…”
Section: Patients' Physiological Statuscontrasting
confidence: 45%
“…The procedures were divided into 3 categories according to surgical complexity (Table 2), using a modified version of the department's own classification: 11 1. A basic procedure is an operation requiring little dissection and/or reconstruction.…”
Section: Robotic Proceduresmentioning
confidence: 99%
“…In our study, we observed a lower rate of serious postoperative complications and a shorter LOS in comparison to the published literature, 25 , 30 , 42 which is suggestive of faster recovery and less tissue trauma. There are several studies demonstrating the feasibility, safety, and good short‐term outcomes of robotic surgery in elderly gynaecologic patients, 27,28 but currently there is limited evidence regarding the safety and efficacy of robotic colorectal surgery in elderly cohorts 29,30 …”
Section: Discussionmentioning
confidence: 99%
“…The possibility of 3D views and 360° instruments rotation allows for a considerable improvement in clinical practice. Many studies have confirmed the safety and feasibility of Robotic Surgery (RS) in all its applications [ 1 ]. Despite the device being initially meant for cardiac surgery, recent years have witnessed a rapid growth in its application to abdominal surgery by urologists, gynaecologists, and general surgeons.…”
Section: Introductionmentioning
confidence: 99%